Biomethanization of the organic fraction of municipal solid wastes - Mata-Alvarez, Joan, ....- (London : IWA publishing, 2003)
1.Fundamentals of the anaerobic digestion process 2.Reactor sizing, process kinetics, and modelling of anaerobic digestionof complex waste 3.Analysis and optimisation of the anaerobic digestion of the organicfraction of municipal solid waste 4.Anaerobic digestion of the organic fraction of municipal solid waste:a perspective 5.Types of anaerobic digester for solid wastes 6.Characteristics of the OFMSW and behaviour of the anaerobic digestionprocess 7.Co-digestion of the organic fraction of municipal waste with otherwaste types 8.Pretreatments for the enhancement of anaerobic digestion of solidwastes 9.Use of hydrolysis products of the OFMSW for biological nutrientremoval in wastewater treatment plants 10.Products, impacts and economy of anaerobic digestion of OFMSW 11.Anaerobic digestion of organic solid waste in bioreactor landfills
Keywords: Agrotechnology and Food Sciences. Engineering -- Waste treatment